Awareness on breast cancer among females at Bharatpur metropolitan, Chitwan, Nepal - Neupane, Laxmi; Upadhyay, Hari Prasad; Chhetri, Chandrakala (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Breast cancer is the most frequently diagnosed cancer in the world and second most common malignancy among Nepalese women with high prevalence. Countries with lower level of resources like Nepal, prevention of breast cancer is more important. The objective of the study was to find out the level of awareness on breast cancer among female at Bharatpur Metropolitan, Nepal. Methods: An analytical cross- sectional study was conducted among 263 female of Bharatpur Metropolitan city, Nepal. Non probability purposive sampling technique was used for data collection. Data was entered and analyzed by using SPSS-20, p-value <0.05 was considered as statistically significant. Results: The mean±SD of age was found 34.40±11.42 years. Study showed that 61.2% (with 95% CI as 55.32-67.1%) had good awareness on risk factors, 60.5% (with 95% CI as 54.54-66.36) had good awareness on warning sign and symptoms and only 44.5% (with 95% CI as 38.48-50.49) had good awareness on screening and prevention. Overall level of awareness on breast cancer was found poor (50.2%). The mean+SD of overall awareness of the respondents on breast cancer was 15.51±2.84. Statistical significant association was found between overall level of awareness and respondents’ education (p=0.039), husband education (p=0.011) and occupation (p=0.046) of the respondents. Conclusions: More than half of the respondents has poor level of awareness on breast cancer among women in Bharatpur, Chitwan, Nepal. Better health awareness among women in the community, breast cancer screening programmes and national policies to establish effective cancer literacy programs would cause a favorable and positive clinical picture in the country.